Optimalisasi penerapan Automatic Exchange of Information (AEoI) dalam mendorong pendapatan negara atas pungutan pajak penghasilan - Muh. Afdal Yanuar (Directorate General of Taxes, 2023)
This study will explore the existence of Automatic Exchange of Information (AEoI) in the Taxation System in Indonesia, and its role in encouraging income tax in Indonesia. The background of this research is based on the idea that income tax is a tax on increasing wealth, and the Automatic Exchange of Information as an instrument in order to support the trace for the increase in the wealth of each taxpayer, by disclosing the bank account information of every taxpayer, both domestically and in other countries. This research is a normative research by using a conceptual approach and a statute approach. The results of this study are that the Automatic Exchange of Information in the taxation system has a position as a balancing instrument, for the possibility for taxpayers to do tax avoidance on their annual tax reports, by breaking through to the confidentiality aspect. In addition, if the Automatic Exchange of Information policy runs optimally, it will be simultaneously with optimalization of income tax.